Integrating science for water security governance - Kristen M. Whitney; Rebecca M. Peters; Anil Mishra; Annalise G. Blum; Perry C. Oddo; Kate A. Brauman; Angelica L. Gutierrez; John D. Bolten; Matthew J. McCarthy; Andrés Sánchez (Global Environmental Change, 2026)

Estimating coral reef carbonate budgets using Structure-from-Motion photogrammetry - Hannah C. Barkley; Ariel A. Halperin; Damaris Torres-Pulliza; Mia S. Lamirand; Courtney S. Couch; Candace E. Alagata; Rebecca M. Weible; Joy N. Smith; Thomas A. Oliver; Chris T. Perry (Coral Reefs, 2025)

Survival, Travel Time, and Use of Migration Routes by Juvenile Steelhead in a Modified River Estuary - Adam C. Pope; Russell W. Perry; Dalton J. Hance; Rebecca A. Buchanan (Estuaries and Coasts, 2025)

A comparative analysis of five commonly implemented declustering algorithms - Mason Perry; Rebecca Bendick (Journal of Seismology, 2024)

Diné-centered research reframes the Gold King Mine Spill: Understanding social and spiritual impacts across space and time - Rebecca J. Clausen; Carmenlita Chief; Nicolette I. Teufel-Shone; Manley A. Begay; Perry H. Charley; Paloma I. Beamer; Nnenna Anako; Karletta Chief (Journal of Rural Studies, 2023)

The effect of exercise on left ventricular global longitudinal strain - James Murray; Hunter Bennett; Eva Bezak; Rebecca Perry; Terry Boyle (European Journal of Applied Physiology, 2022)
Exercise improves measures of cardiovascular (CV) health and function. But as traditional measures improve gradually, it can be difficult to identify the effectiveness of an exercise intervention in the short-term. Left ventricular global longitudinal strain (LVGLS) is a highly sensitive CV imaging measure that detects signs of myocardial dysfunction prior to more traditional measures, with reductions in LVGLS a strong prognostic indicator of future CV dysfunction and mortality. Due to its sensitivity, LVGLS may offer useful method of tracking the effectiveness of an exercise intervention on CV function in the short-term, providing practitioners useful information to improve patient care in exercise settings. However, the effect of exercise on LVGLS is unclear. This systematic review and meta-analysis aimed to determine the effect exercise has on LVGLS across a range of populations. Included studies assessed LVGLS pre–post an exercise intervention (minimum 2 weeks) in adults 18 years and over, and were published in English from 2000 onwards. Study-level random-effects meta-analyses were performed using Stata (v16.1) to calculate summary standardized mean differences (SMD) and 95% confidence intervals (CI). 39 studies met selection criteria, with 35 included in meta-analyses (1765 participants). In primary analyses, a significant improvement in LVGLS was observed in populations with CV disease (SMD = 0.59; 95% CI 0.16–1.02; p = 0.01), however, no significant effect of exercise was observed in CV risk factor and healthy populations. In populations with CV disease, LVGLS could be used as an early biomarker to determine the effectiveness of an exercise regime before changes in other clinical measures are observed.

Site use and connectivity of female grey seals (Halichoerus grypus) around Wales - Izzy Langley; Tobias Rosas da Costa Oliver; Lex Hiby; Thomas B. Stringell; Ceri W. Morris; Oliver O’Cadhla; Lisa Morgan; Kate Lock; Sarah Perry; Stephen Westcott; Dave Boyle; Birgitta I. Büche; et al. (Marine Biology, 2020)
Grey seals ( Halichoerus grypus ) are a qualifying feature of three special areas of conservation (SACs) in Wales, yet relatively little is known of their site use along this coastline. Since 1992, many individuals and organisations have contributed to a grey seal photographic identification database held by Natural Resources Wales, which is one of the largest and oldest of its kind, providing key information from grey seal haul-out sites around the Celtic and Irish Seas. Here, we investigated spatial connectivity of haul-out sites and fidelity of adult females to breeding sites. The minimum number of adult female grey seals using the area between 1992 and 2016 was 2688. Individual capture histories and relative spatial transition probabilities ( P ij ) between pairs of location groups were calculated. Adjacent locations were highly connected (e.g. Lleyn Peninsula and Bardsey, P ij = 0.7) but connections spanned the entire region, up to 230 km apart (e.g. Skomer and Dee Estuary, P ij = 0.004). Resights were recorded within SACs (e.g. Lleyn Peninsula and Bardsey [Lleyn Peninsula and the Sarnau SAC], P ij = 0.7), between SACs (e.g. Bardsey and Skomer [Pembrokeshire Marine], P ij = 0.03), between SACs and non-designated areas (e.g. Skerries and Bardsey, P ij = 0.09) and between sites outside any protected area (e.g. Dee Estuary and Anglesey, P ij = 0.5). While inter-annual fidelity to breeding sites was high ( P ij = 0.82–1), individual female grey seals moved throughout the region. This evidence of extensive site use beyond protected areas is important for the management and conservation of grey seals around Wales.

Floral abundance and richness drive beneficial arthropod conservation and biological control on golf courses - Adam G. Dale; Rebecca L. Perry; Grace C. Cope; Nicole Benda (Urban Ecosystems, 2020)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Improving Environmental Management on Small-scale Farms: Perspectives of Extension Educators and Horse Farm Operators - Perry-Hill Rebecca; Prokopy Linda (Environmental Management, 2015)

Capsaicin induces apoptosis in human small cell lung cancer via the TRPV6 receptor and the calpain pathway - Jamie K. Lau; Kathleen C. Brown; Aaron M. Dom; Theodore R. Witte; Brent A. Thornhill; Clayton M. Crabtree; Haley E. Perry; J. Michael Brown; John G. Ball; Rebecca G. Creel; C. Luke Damron; William D. Rollyson; et al. (Apoptosis, 2014)

Mapping the low palmitate fap1 mutation and validation of its effects in soybean oil and agronomic traits in three soybean populations - Andrea J. Cardinal; Rebecca Whetten; Sanbao Wang; Jérôme Auclair; David Hyten; Perry Cregan; Eleni Bachlava; Jason Gillman; Martha Ramirez; Ralph Dewey; Greg Upchurch; Lilian Miranda; et al. (Theoretical and Applied Genetics, 2014)

Pacific Rim Forestry - Thomas Brandeis; Olaf Kuegler; Robert Pattison; Örjan Jonsson; James Halperin; Kathleen McGinely; Constance Carpenter; Kathleen Friday; Guy Robertson; Nicklos Dudley; Robert James; Richard Sniezko; et al. (Journal of Forestry, 2011)
68Stakeholders' questions about subtropical and tropical forests can be as diverse and unique as the forests themselves. Obtaining the information needed to begin answering these questions requires innovation and adaptation of existing forest mensuration and inventory techniques that were developed primarily for use in temperate and boreal forests with a strong forest industry presence. Five cycles of forest inventory and monitoring in Puerto Rico and two cycles in the US Virgin Islands under the Forest Inventory and Analysis (FIA) program highlight the commonalities and differences between working in these subtropical forests and the temperate forests of the continental United States. Additionally, the Caribbean implementation of the FIA program has often taken a different approach from that used in the Pacific Islands territories. We can improve on delivery of forest resource information to island stakeholders by studying these experiences. By sharing the lessons learned with other Pacific Rim countries engaging in forest inventory and monitoring, we can learn from each other.

Pervious and Impervious Urban Stormwater Runoff in a Rapidly Urbanizing Region: Occurrence of Fluoranthene and Pyrene - Rebecca R. James; Perry Wilbon; John P. DiVincenzo (Bulletin of Environmental Contamination and Toxicology, 2010)

Effects of haloperidol on the behavioral, subjective, cognitive, motor, and neuroendocrine effects of Δ-9-tetrahydrocannabinol in humans - Deepak Cyril D’Souza; Gabriel Braley; Rebecca Blaise; Michael Vendetti; Stephen Oliver; Brian Pittman; Mohini Ranganathan; Savita Bhakta; Zoran Zimolo; Thomas Cooper; Edward Perry (Psychopharmacology, 2008)